Early Greek legal history and the Mycenaean sources (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2024)
Legal historians of ancient Greece often begin with the Homeric poems as the earliest sources for a study of the emergence of normative order in Greece. By contrast, the large corpora of administrative records produced by the Mycenaean palaces from ca. 1450-1200 BC have aroused little interest in the legal historiography. Despite this, discussions of themes such as property, relations of obligation, and dispute resolution are prominent in the specialist Mycenaean literature, but often with uncritical and selective reliance on legal conceptions. This paper outlines several key problems for a legal historical approach to the Mycenaean evidence, through a critical consideration of the reasons why these sources have long been excluded by legal historians. It is argued that a legal historical approach must avoid applying formalist conceptions of law and legal categories to the Mycenaean evidence, and must engage with trends in specialist studies which have recognised a more limited role of the Mycenaean palaces in the broader economy. Following the example of recent critical histories of the production of normativity in other premodern contexts, this article outlines some key considerations for a legal history of the Mycenaean world and emphasises the broader social and economic context of the administrative practices which produced the documentary records. It is argued that the evidence should not merely be read from the perspective of the palace as the only centre of order, but that the records reveal limitations to the scope of palatial normativity, especially in the sphere of property relations where the local communities held considerable power. This article calls for future studies of the Mycenaean records to adopt a more pluralistic conception of the production of normativity, and to engage with trends in critical legal historiography.
Keywords: ancient Greek law; Mycenean civilization; Linear B; administrative documents; legal theory; historiography